Behavior of bowhead whales, Balaena mysticetus, summering in the Beaufort Sea: surfacing, respiration, and dive characteristics - Würsig, Bernd; Dorsey, Eleanor M.; Fraker, Mark A.; Payne, Roger S.; Richardson, W. John; Wells, Randall S. (Canadian Journal of Zoology, 1984)
Surfacing, respiration, and dive characteristics are described for presumably undisturbed bowhead whales in the Beaufort Sea during August and early September 1980–1982. The interval between respirations (blow interval) was relatively constant during different activities such as skim feeding at the surface, social interactions, and feeding in the water column. Durations of adjacent surfacings and dives were positively correlated, and number of blows per surfacing was correlated with duration of surfacing. Mean blow interval, number of blows per surfacing, duration of surfacing, and duration of dive were all greater in 1982 than in the previous 2 years, presumably because of increased feeding in the water column in 1982. Blow rates were lower in 1982 than in 1980–1981, possibly due to less socializing in 1982. There was a tendency for increased dive durations in deeper water, but the data were not consistent on this point. In general, calves exhibited short dives and surfacings, especially while nursing. Nursing mothers were inactive and had lower blow rates than other adults.